Parameters analysis and process optimization of shell precision thermoforming - Cheng Haozhe; Xu Shubo; Sun Kangwei; Wang Shengliang; Pan Yuefei; Ma Hailong; Ren Guocheng; Li Jianing; Zhao Zhongkui (International Journal for Simulation and Multidisciplinary Design Optimization)
In this study, the aluminium alloy shell forming process is firstly studied and analysed. After that, the three-dimensional modelling software SOLIDWORKS is used to analyse and model the workpieces and the convex and concave dies of each process of the aluminium alloy shell hot extrusion forming process. Finally, the three-dimensional finite element numerical simulation software DEFORM-3D is used to carry out numerical simulation analysis on the precision hot forming process of aluminium alloy shell. Equivalent force and strain distributions, along with stroke-load curves, were analyzed under varying conditions by changing the friction factor and forming temperature. The simulation results show that under the conditions of friction factor of 0.25 and temperature of 450 °C, it is most suitable for the machining of aluminium alloy shell hot extrusion forming process.